2009
DOI: 10.1681/asn.2008050450
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory, Effector, and Cytotoxic T Cell Profiles in Long-Term Kidney Transplant Patients

Abstract: Animal studies have suggested a potential role for regulatory T cells (Tregs) in allograft tolerance, but these FOXP3ϩ cells seem to be an inherent component of acute rejection (AR) in human recipients of renal transplants. The balance between regulatory cells and effector/cytotoxic cells may determine graft outcome; this balance has not been described for chronic allograft injury. We investigated the expression of key regulatory, effector, and cytotoxic transcripts (i.e., FOXP3, T-bet, and granzyme B, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
53
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 32 publications
5
53
0
1
Order By: Relevance
“…18 Thus, the ratio of intragraft T-bet/GATA3 could be a useful adjunct to C4d staining in the diagnosis ABMR. Our findings are at least consistent with intraglomerular T-bet predominance in chronic ABMR reported by AshtonChess et al, 10 although GATA3 expression was not assessed in that study. The key difference in T-bet/GATA3 expression in ABMR and TCMR is not on the overall quantity but the localization.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…18 Thus, the ratio of intragraft T-bet/GATA3 could be a useful adjunct to C4d staining in the diagnosis ABMR. Our findings are at least consistent with intraglomerular T-bet predominance in chronic ABMR reported by AshtonChess et al, 10 although GATA3 expression was not assessed in that study. The key difference in T-bet/GATA3 expression in ABMR and TCMR is not on the overall quantity but the localization.…”
supporting
confidence: 93%
“…9 Moreover, the predominance of intraglomerular T-bet has also been observed in patients with antibodymediated chronic rejection and transplant glomerulopathy. 10,11 We hypothesized that changes in the expression of T-bet and GATA3 might relate to the pathogenesis of the two types of renal allograft rejection, ABMR and TCMR. This study was performed to determine whether changes of either T-bet or GATA3 expression account for the development of ABMR and TCMR.…”
mentioning
confidence: 99%
“…8 This profile was associated with transcript coding for granzyme B (GZM-B) in the graft. [9][10][11] Similar observations made in the blood of CAMR patients reported a restricted TCR Vb repertoire, an increase in IFN-g, GZM-B, and perforin-1 (PERF-1) transcripts, and an increase in CD8 T cells. [12][13][14] These observations suggest that alteration in the TCR Vb repertoire of CD8 T cells may be associated with kidney dysfunction.…”
supporting
confidence: 65%
“…We then can hypothesize that such peripheral expansions, and particularly in patients with chronic rejection, could be related to dominant indirect [3] or direct [30] alloimmune responses against the graft. The role of T cells and especially CD8 1 T cells had been likely undermined in the process of chronic rejection, whereas several studies confirmed the presence of CD8 1 T cells infiltrate in the graft [31][32][33]. Moreover, we have shown that blood of animals (as reported here in patients) with chronic rejection exhibited strong alteration of the CD8 1 T-cell repertoire [34].…”
supporting
confidence: 50%